On dynamics of a landing gear mechanism with torsional freeplay (Global Journals of Research in Engineering, 2012)
In this study dynamics of a landing gear mechanism with torsional degree of freedom and torsional freeplay is analyzed Derivation of the equations of motion of the model with torsional degree of freedom and the von Schlippe tire model are presented Freeplay is introduced into the model and effects of freeplay angles of 0 0 5 1 and 1 5 are observed by obtaining time histories of the torsion angle and lateral tire deformation and limit cycles of the torsionangle Amplitudes and frequencies of oscillations of the time histories of the torsion angle and lateral tire deformation are presented
Keywords: dynamics; torsional; Derivation; angles; histories; oscillations